Dynamic Sub-Array Selection-Based Energy-Efficient Localization and Tracking Method to Power Implanted Medical Devices in Scattering Heterogenous Media Employing Ultrasound - Parag, Anirudh Kumar; Raducanu, Bogdan C.; Erden, Oguz Kaan; Stanzione, Stefano; Beutel, Fabian; Pendse, Chinmay; Van Hoof, Chris; Van Helleputte, Nick; Gielen, Georges (IEEE transactions on biomedical circuits and systems, 2025)
Ultrasound (US) as a wireless power transfer methodology has drawn considerable attention from the implantable medical devices (IMD) research community. Beamforming (BF) using an external transducer array patch (ETAP) has been proposed as a robust localization scheme to find a mm-sized IMD inside the human body. However, for applications focusing on deep and shallow IMDs, optimum resource utilization at the ETAP is a major power efficiency concern for energy-constrained wearable patches. Moreover, misalignment tolerance due to IMD movements (respiratory and patient ambulatory reasons) relative to the ETAP remains a challenge. This paper presents an energy-efficient method to localize a mm-sized IMD through the dynamic selection of a sub-array within the ETAP. It is fully adaptive to the heterogeneity of the media and requires no a priori knowledge of the IMD. To improve the tolerance to IMD movements, tracking is implemented by adding and subtracting elements on the sub-array such that the sub-array electrically follows the IMD movement. Furthermore, it is shown that a minimum sampling frequency of 10X the US frequency can improve the tolerance to random noise. K-wave simulations in MATLAB are performed in different heterogenous, scattering biological media to prove the efficacy of the proposed method over standard BF methods. Measurement results in heterogenous scattering media consisting of a 3D-printed human ribs phantom and a partially blocking multipath cancellous bone phantom show an energy efficiency improvement of 10.53X and 14.4X compared to the delay-and-sum beamforming method and the unfocused transmission employing all the elements of the ETAP, respectively.